2005
DOI: 10.1007/s11208-005-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Dust Particles and Delivery of Volatiles to the Terrestrial Planets

Abstract: Results of computer simulations of the migration of small bodies and dust in the Solar System showed that a relative fraction of cometary and trans-Neptunian dust particles in the total balance of the dust encountering the terrestrial planets can be significant. The contribution of dust particles to the delivery of volatiles to the terrestrial planets is estimated to be 3-4 orders of magnitude less than that of small bodies. However, the dust particles could be most efficient in the delivery of organic or even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In different runs of calculations, the integration step was varied from 10 to 30 days and was constant in each of the runs. Earlier, we considered the evolution of orbits of more than 30000 bodies with initial orbits close to those of Jupiter-family comets (JFC), comet Halley, longperiod comets and asteroids under the 3/1 and 5/2 resonances with Jupiter, and more than 20000 dust grains produced by these small bodies (Marov and Ipatov, 2005;Ipatov and Mather, 2004Ipatov, 2010). In our previous calculations, we used the Bulirsch-Stoer algorithm (BULSTO) and the symplectic method of integration, which yielded almost the same results.…”
Section: Initial Data and Algorithms To Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In different runs of calculations, the integration step was varied from 10 to 30 days and was constant in each of the runs. Earlier, we considered the evolution of orbits of more than 30000 bodies with initial orbits close to those of Jupiter-family comets (JFC), comet Halley, longperiod comets and asteroids under the 3/1 and 5/2 resonances with Jupiter, and more than 20000 dust grains produced by these small bodies (Marov and Ipatov, 2005;Ipatov and Mather, 2004Ipatov, 2010). In our previous calculations, we used the Bulirsch-Stoer algorithm (BULSTO) and the symplectic method of integration, which yielded almost the same results.…”
Section: Initial Data and Algorithms To Modelmentioning
confidence: 99%
“…The exogenous sources could originate from the migration of bodies from the outer part of the Main asteroid belt (O'Brien et al, 2014;Morbidelli et al, 2000Morbidelli et al, , 2012Petit et al, 2001;Raymond et al, 2004;Lunine et al, 2003Lunine et al, , 2007 and migration of planetesimals from beyond Jupiter's orbit (Morbidelli et al, 2000;Levison et al, 2001;Marov and Ipatov, 2001;2005;Ipatov and Mather, 2004Ipatov, 2010). For the Grand Tack model, Rubie et al (2015) considered the migration of planetesimals from a zone of 6−9.5 AU.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the volatile and moderately volatile components were deficient in the iner regions of the solar system. According to the models developed [42] [43] the bulk of Earth's ad terrestrial planets water was obtained later on through migration of volatile-rich objects (comets ad asteroids) from the outer regions of the solar system, mainly from its outskirt in the Kuiper belt, which was responsible for heterogeneous accretion of these planets mostly during period of the Late Heavy Bombardment (LHB).…”
Section: Gas-dust Protoplanetary Disc Evolutionmentioning
confidence: 99%
“…Small bodies which collided with planets could deliver volatiles and organic/prebiotic compounds needed for life origin. Marov & Ipatov (2005) concluded that dust particles could be most efficient in the delivery of organic or even biogenic matter to the Earth, because they experience substantially weaker heating when passing through the atmosphere (an excess heat is radiated effectively due to high total surface-to-mass ratio for dust particles). They assumed that life forms drastically different from the terrestrial analogs are unlikely to be found elsewhere in the solar system (if any), e.g., either extinct or extant life on Mars.…”
Section: Delivery Of Water and Volatiles To Planetsmentioning
confidence: 99%